COUNTERING EXTREMISM AND TERRORISM IN THE ACTIVITIES OF INTERNATIONAL ORGANIZATIONS: POLITICAL AND LEGAL ASPECT - B. G. Koybaev (Современная наука и инновации)
The article considers the political and legal activities of international organizations such as the UN, PACE and the SCO on countering extremist and terrorist manifestations in the modern world. Attempts to identify the positive experience of these organizations in solving theoretical and practical problems of eradication of extremist practices